OCCURRENCE OF ISOPARORCHIS HYPSELOBAGRI (Billet, 1898) F. MORAVEC, (1989) (Family: ISOPARORCHIIDAE POCHE, 1926) AS PARASITE OF FRESH WATER FISH MASTACEMBELUS ARMATUS (LACEPEDE, 1800) IN SINA KOLEGOAN DAM, OSMANABAD DISTRICT (MS) - Jadhav, Swati; Humbe, Atul; Borde, Sunita (IJRDO-Journal of Applied Science, 2016)
The present investigation was carried out on helminth parasites of Sina Kolegoan Dam,Osmanabad District. The Metacercaria of Isoparorchis hypselobagri (Billet, 1898) Odher, 1927was described from the Air bladder of fresh water fish Mastacembelus armatus (Lacepede,1800)from Sina kolegoan Dam dist Osmanabad (MS), India during January, 2011. Isoparorchishypselobagri characterized by having Body large, oval, narrow at both the ends wide in themiddle, leaf like, dorsoventrally flattened, reddish in colour. Oral sucker oval, Ventral suckeroval in shape, larger than oral sucker. Intestinal caeca elongated, bifurcate, bulging at somewhatfew distance. Gonopore small rounded. Testis are small, oval, two in numbers. Cirrus pouchoval, large. Ovary is branched, irregular in shape. Uterus is large or much coiled broad. Eggs areelongated. Vitellaria median. Excretory vesicle is ‘Y’ shaped